Enamel print pattern in Deutero-Malay sub race based on extracted female permanent maxillary central incisors - Huat, Tan Kien; Dardjan, Murnisari; Yohana, Winny (Universitas Padjadjaran, 2020)
Introduction: Enamel print pattern is a series of lines representing the enamel rod ends pattern. These lines are seen running in varying directions creating distinct sub-patterns; thus, enamel print pattern allows for personal identification. This study was aimed to investigate the enamel print pattern in Deutero-Malay sub race based on extracted female permanent maxillary central incisors. Methods: This study used descriptive-analytic methods. The population of this study was Deutero-Malay sub-race female individuals who came to Batu Pahat Dental Surgery, Johor, Malaysia. The samples were 31 post-extracted permanent maxillary central incisors teeth in good condition, with closed root apex. Photomicrographs and a digital photo of samples were taken, then analysed using SourceAFIS-1.7.0 biometric software. Results: The results showed that there was a combination of few sub-patterns. The most prominent sub-pattern was linear-branched (21.36%), in decreasing orders of prominence were the wavy-branched (19.42%), wavy-unbranched (16.50%) and linear-unbranched (15.53%). The less common sub-patterns were the whorl-open (9.71%), loop (6.80%), whorl-closed (5.83%) and stem-like (4.85%). Conclusion: The enamel print pattern in every central incisor has no similarity; hence can be a possible tool for personal identification.